2020
DOI: 10.1007/s12325-020-01255-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nurse Preferences Between the Lanreotide Autogel New Syringe and the Octreotide Long-Acting Release Syringe: An International Simulated-Use Study (PRESTO)

Abstract: Introduction: Somatostatin analogues are used to treat symptoms and slow tumour progression in patients with neuroendocrine tumours (NETs) and carcinoid syndrome and to reduce hormone secretion and pituitary tumour Enhanced Digital Features To view enhanced digital features for this article, including a summary slide and graphical abstract, go to https://doi.org/10.6084/m9. figshare.11806605. Electronic Supplementary Material The online version of this article (https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…The survey design was based on concepts identified from the previous preference studies [ 18 20 ] and a gap analysis of the published literature, as well as input from an advisory board consisting of an expert on patient-reported outcomes (PROs), physicians and nurses. Before the survey was launched, validity of the questionnaire was tested through a cognitive debriefing with patients with NETs ( n = 3) and acromegaly ( n = 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey design was based on concepts identified from the previous preference studies [ 18 20 ] and a gap analysis of the published literature, as well as input from an advisory board consisting of an expert on patient-reported outcomes (PROs), physicians and nurses. Before the survey was launched, validity of the questionnaire was tested through a cognitive debriefing with patients with NETs ( n = 3) and acromegaly ( n = 2).…”
Section: Methodsmentioning
confidence: 99%
“…For OCT, the diluent used in the syringe was reformulated to facilitate its preparation and administration, resulting in fewer administration problems than with the previous formulation, improved ease of use and overall increased nurse satisfaction [ 17 ]. The PRESTO simulated-use study, conducted in 2019, found that nurses preferred the redesigned LAN syringe to the OCT syringe with the reformulated diluent, particularly in terms of the faster speed of administration and greater confidence that the LAN syringe will not become clogged [ 18 ]. However, no studies have explored the real-world preference or opinions of patients using the latest proprietary LAN and OCT devices and formulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a recent observational study, 4% of nurses ( n = 96) reported that purge problems (clogging) persisted when injecting OCT LAR reconstituted with the new solvent [ 48 ]. Further, in an international simulated-use study (PRESTO), also completed since this SLR was conducted, most nurses (88/90) expressed a “slight” or “strong” preference for the LAN new syringe vs the OCT LAR syringe (with the latest excipient), citing “confidence the syringe will not be clogged” as the most important attribute [ 49 ]. This factor may also impact patients’ treatment experience; a recent survey conducted in 2019 found that patients’ overall SSA injection experience is also impacted by the training and process knowledge of their HCP, leading to variation in patient satisfaction depending on the nurse administering the SSA [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…В итоге лекарственная форма не нуждается в дополнительных ингредиентах, а содержит только плотно упакованный пептид и воду, что позволяет вводить очень небольшие объемы даже для высоких доз препарата, способного высвобождать активное лекарство контролируемым образом в течение длительного периода времени. Наличие заполненного шприца, малые объемы вводимого вещества, возможность самостоятельного введения и оперативного изменения межинъекционных интервалов способствовали повышению приверженности пациентов лечению [9,10].…”
Section: аналоги соматостатина 1-й генерацииunclassified
“…Пэгвисомант (Сомаверт) можно использовать в качестве монотерапии (при небольших размерах аденомы) или в комбинации с АС либо каберголином. 10 Для пациентов с исходно высокой гормональной активностью, сахарным диабетом, повышенным индексом массы тела требуются более высокие стартовые дозы и ускоренная титрация лекарственного препарата для нормализации ИФР-1 [38]. Показанием для назначения пэгвисоманта будет сохранение активности заболевания после нерадикальной аденомэктомии и вторичной медикаментозной терапии АС1.…”
Section: антагонист рецепторов гормона ростаunclassified